XPS study from a clean surface of Al2O3 single crystals. (2017) - TAGO, Tuguhiro; KATAOKA, Noriyuki; TANAKA, Hiromi; KINOSHITA, Kentaro; KISHIDA, Satoru
Abstract: It is necessary to understand chemical bond nature of constituent elements on surfaces of Al alloy and Al2 O3 single crystals for the fabrication of electronic devices and the advanced technology of etching agent. In this study, we used as-sliced Al2 O3 single crystals and investigated the chemical state on various surfaces of the Al2 O3 single crystal with a high-resolution X-ray photoelectron spectroscopy (XPS). As a result, we obtained the XPS spectra from the surfaces of as-annealed, monoatomic Ar + -etched and Ar + (500)-GCIB (gas cluster ion beam)-etched Al2 O3 single crystals. From the results, we found that the XPS spectra of Al-2s and O-1s core levels from the clean surface of Al2 O3 single crystals, which has not elements except Al and oxygen, and an ideal stoichiometry of Al2 O3, were obtained. In addition, there were Al metal on the surface of Al2 O3 single crystal by hydroxide (OH-) on the as-annealed surface of the single crystals. It is not easy to get a clean surface of Al2 O3 single crystal, especially oxides. However, by etching the surface with the cluster of Ar + 500 for 720 sec, Al-2p and O-1s XPS spectra from the clean surface which were different from those by etching with monoatomic Ar +, were obtained.